THE BLOOD FLOWS IN THE LEFT VENTRICLE AS PREDICTORS FOR MYOCARDIAL DYSFUNCTION IN DILATED CARDIOMYOPATHY - V. A. Sandrikov; T. Yu. Kulagina; A. S. Krylov; A. M. Yatchenko (Российский кардиологический журнал, 2014)
Aim. To evaluate the treatment results and to estimate the early predictors for myocardial dysfunction in patients with DCMP.Material and methods. Totally 69 patients with DCMP (median age 42±14) were investigated before and after operation. Patients were divided into 3 groups: 1st — 69 patients before surgical treatment; 2nd — 41 patients those who were examined in 9-12 months after operation; 3rd — patients being monitored for more than 24 months after operation. The control consisted of 110 volunteers with the menian age 37±8 y.o.To all patients the echocardiography was applied using expert class Vivid E9 (GE, USA) machine with multifrequency sensor 3,5-5,0 MHz. To visualize flows in the left ventricle the flow velocity was registered in the areas of fiber ring, middle and apical areas.Results. With the LV function disturbing in DCMP patients the rise of pre- and postload causes significant changes in myocardial functioning. The direction of blood flow in the LV significantly changes with hypertrophy of myocardium and papillary muscles, valve dysfunction and other disorders. We had concluded that in DCMP, at the same time with high EDV and ESV there is incessance of blood flow which determines heart work by continuous blood motion, elasticity of magistral vessels and myocardium contraction.By echocardiography and computed tomography it was found that heart rotation is in order from the right to the left segments of basal area and then to descending and ascending segments of the heart apex.Conclusion. The velocity of myocardial shifts, of blood flows in the LV make possible to evaluate heart functioning in patients with heart failure and to estimate the effectiveness of surgical treatment in closer and further postoperational periods. Basing on the measurements of blood flows in heart chambers and on estimation of intraventricular pressure gradients (from the apex to basement) it is possible to analyse the functioning and the performance of valves in patients with DCMP. The appearance in LV of additional turbulent flows, the decrease of flow velocity during the cardiac contraction cycle in one or another part are responsible for the failure and can be regarded as early predictors of myocardial dysfunction.